Educação financeira: uma abordagem necessária em aulas de matemática no ensino médio - CARMO, Alvaro Rodrigo Pompeu do (2022)
This research aims to present propositional activities that are aligned with bncc descriptors that help in the curricular composition on Financial Education for High School, from the perspective of Active Methodologies. To obtain the data, we used books by well-known authors with related themes and government websites, among others, which dealt with financial education in elementary school, directing later to high school. Through deepening, it was shown the need to develop in students the ability to manage their income both in the present, with the change of attitudes, as well as in the future through personal and family budget, to the responsibility of living in a consumer society and their awareness that their financial choices directly or indirectly affect the environment in which they live. Proposed activities were elaborated, which aims to explore Financial Education across the board, making the most of the concept of Financial Education throughout high school. The research concludes that it is possible to use the active methodologies both those described in this work, and those that are still being explored from the perspective of financial learning, to facilitate the insertion of Financial Education.